Enrichment of Glial Cells From Human Post-mortem Tissue for Transcriptome and Proteome Analysis Using Immunopanning - Nolle, Anna; van Dijken, Irene; Waelti, Ciril M.; Calini, Daniela; Bryois, Julien; Lezan, Emmanuelle; Golling, Sabrina; Augustin, Angelique; Foo, Lynette; Hoozemans, Jeroen J. M. (Frontiers in Cellular Neuroscience, 2021)
Glia cells have a crucial role in the central nervous system and are involved in the majority of neurological diseases. While glia isolation techniques are well established for rodent brain, only recent advances in isolating glial cells from human brain enabled analyses of human-specific glial-cell profiles. Immunopanning that is the prospective purification of cells using cell type-specific antibodies, has been successfully established for isolating glial cells from human fetal brain or from tissue obtained during brain surgeries. Here, we describe an immunopanning protocol to acutely isolate glial cells from post-mortem human brain tissue for e.g. transcriptome and proteome analyses. We enriched for microglia, oligodendrocytes and astrocytes from cortical gray matter tissue from three donors. For each enrichment, we assessed the presence of known glia-specific markers at the RNA and protein levels. In this study we show that immunopanning can be employed for acute isolation of glial cells from human post-mortem brain, which allows characterization of glial phenotypes depending on age, disease and brain regions.